Hypothyroidism/subclinical hypothyroidism and metabolic dysfunction-associated steatotic liver disease: advances in mechanism and treatment - Sicheng Pu; Binbin Zhao; Yuxuan Jiang; Xuejiao Cui (Lipids in Health and Disease, 2025)
Abstract Hypothyroidism is a risk factor for metabolic dysfunction-associated steatotic liver disease (MASLD) but it is not clear whether subclinical hypothyroidism (SCH) increases the risk of MASLD and whether SCH patients with MASLD require treatment. In this study, we reviewed articles published in PubMed from 2013 to 2024 with SCH/hypothyroidism and MASLD as keywords. According to the studies retrieved, SCH increases the likelihood of developing MASLD. Thyroid hormones influence energy metabolism and storage in adipose tissues, as well as fatty acid and cholesterol metabolism and transport in the liver. L-T4 replacement therapy reduces the prevalence of MASLD, especially in patients with severe SCH or mild SCH with dyslipidemia. Recent studies showed that thyroid hormone analogues and thyroid hormone β receptor agonists obtained positive results in the treatment of MASLD in animal models and clinical trials, and Resmetirom has been approved by the US. Food and Drug Administration (FDA) under the name Rezdiffra for use in conjunction with dietary and exercise regimens for managing non-cirrhotic NASH in adults with moderate to advanced fibrosis.